2020
DOI: 10.48550/arxiv.2008.12090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The minimal seesaw and leptogenesis models

Zhi-zhong Xing,
Zhen-hua Zhao

Abstract: Given its briefness and predictability, the minimal seesaw -a simplified version of the canonical seesaw mechanism with only two right-handed neutrino fields -has been studied in depth and from many perspectives, and now it is being pushed close to a position of directly facing experimental tests. This article is intended to provide an up-to-date review of various phenomenological aspects of the minimal seesaw and its associated leptogenesis mechanism in neutrino physics and cosmology. Our focus is on possible… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 213 publications
(321 reference statements)
1
25
0
Order By: Relevance
“…It is found that the areas of such sub-triangles can be described in terms of the Jarlskog-like invariants of CP violation J ij αβ , and their small differences may serve as a signal of slight unitarity violation of the 3 × 3 PMNS matrix U . These observations should be useful to test the unitarity of U when more accurate experimental data are available in the foreseeable future, and they can certainly be extended to those simplified seesaw cases (e.g., the minimal seesaw scenarios [49]) with fewer free parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the areas of such sub-triangles can be described in terms of the Jarlskog-like invariants of CP violation J ij αβ , and their small differences may serve as a signal of slight unitarity violation of the 3 × 3 PMNS matrix U . These observations should be useful to test the unitarity of U when more accurate experimental data are available in the foreseeable future, and they can certainly be extended to those simplified seesaw cases (e.g., the minimal seesaw scenarios [49]) with fewer free parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Best fit 1σ range 3σ range σ i Normal neutrino mass ordering (m 1 < m 2 < m 3 ) sin 2 [80][81][82][83][84][85][86] and assign two right-handed neutrino singlets into the two-dimensional representation of Γ 5 . Two concrete examples in the MSM have been given to explain the observed pattern of lepton flavor mixing.…”
Section: Parametermentioning
confidence: 99%
“…However, such a representation obscures symmetries and relationships of the original Lagrangian. Thus, in this letter, we analyze the conditions for CP symmetry of the light neutrino mass matrix m in the minimal seesaw model [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] using a formula by LDL T decomposition [24]. As a result, basis-independent conditions are obtained for the general Lagrangian parameters.…”
Section: Introductionmentioning
confidence: 99%